CYTOPLASMIC ATP-DEPENDENT REGULATION OF ION TRANSPORTERS AND CHANNELS: Mechanisms and Messengers - Hilgemann, Donald W. (Annual Review of Physiology, 1997)
▪ Abstract Many ion transporters and channels appear to be regulated by ATP-dependent mechanisms when studied in planar bilayers, excised membrane patches, or with whole-cell patch clamp.Protein kinases are obvious candidates to mediate ATP effects, but other mechanisms are also implicated. They include lipid kinases with the generation of phosphatidylinositol phosphates as second messengers, allosteric effects of ATP binding, changes of actin cytoskeleton, and ATP-dependent phospholipases. Phosphatidylinositol-4,5-bisphosphate (PIP2) is a possible membrane-delimited messenger that activates cardiac sodium-calcium exchange, KATP potassium channels, and other inward rectifier potassium channels. Regulation of PIP2 by phospholipase C, lipid phosphatases, and lipid kinases would thus tie surface membrane transport to phosphatidylinositol signaling. Sodium-hydrogen exchange is activated by ATP through a phosphorylation-independent mechanism, whereas ion cotransporters are activated by several protein kinase mechanisms. Ion transport in epithelium may be particularly sensitive to changes of cytoskeleton that are regulated by ATP-dependent cell signaling mechanisms.
Keywords: phosphorylation